Persepsi Dan Aktivitas Pascapersepsi Mahasiswa FKIP Unitomo Terhadap Dakwah Di Media Sosial - Nuril Huda; Sumartono; Ninik Mardiana (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
Stems from the development of all-digital technology and the rapid development of the world of communication led to a shift in media propaganda in the community. From the creations on sosial media, it creates various perceptions for message recipients or sosial media connoisseurs. With descriptive quantitative method, this study took a sample of 40 questionnaires by random sampling. The instrument used in the form of a questioner with questions that require open and closed answers. The results obtained by all respondents had received propaganda posts in various forms and expressed benefits to a certain degree and easy to understand. As many as 21% of respondents ignored the propaganda posts. There are 59% of respondents consider direct propaganda is more effective than through sosial media.